The Psychological Adjustment of Children with Asthma: Study of Associated Variables - Lima, Ligia (2010)
As part of a larger research project aimed to understand the impact of asthma in the psychological adjustment of children, this study focuses in the identification of factors associated with this process. The sample of this study consisted of 89 children, aged 8 to 12 with physician diagnosed asthma. To assess children’s adjustment, the Portuguese versions of the following instruments were used: School-age Temperament Inventory (McClowry, 1995) Schoolagers Coping Strategies Inventory (Ryan-Wenger, 1990); Pediatric Quality of Life Inventory – PedsQL (Varni, Seid & Kurtin, 2001); The Self-perception Profile for Children (Harter, 1985), Child Behavior Checklist (Achenbach,1991); Social Skills Rating System (Gresham & Elliot, 1990). The results revealed that negative reactivity predicts the level of anxiety/depression, task persistence and perceived coping efficacy predicts social skills and that self-esteem is a significant predictor of the perceived quality of life. A significant proportion of shared variance was also found what seems to confirm the existence of multi-determination in the process of adjustment. The main conclusion is that two dimensions of temperament (negative reactivity and task persistence), as well as perceived coping efficacy and self-esteem, play a significant role in influencing the psychological adjustment of children with asthma.